Study of erosion on the neutron activate analysis of the fixed soil core Eu tracer on red soil slope - MA Kun; WANG Zhao-qian; CHEN Xin; SUI Guo-ping; YANG Sui-ping (浙江大学学报. 农业与生命科学版, 2003)
The method of setting and sampling of fixed soil core Eu tracer were studied by combination of rainfall simulation and a runoff plot. The result showed that the method of fixed soil core Eu tracer associated with the Instrument Neutron Activate Analysis (INAA) technique could be used to determine soil erosion in different topography site exactly. The tendency of soil loss per area on red soil slope using Er-Es experiential model was predicted. The maximum error between the actual soil loss and the result predicted by model was about 6.71 t/hm2. The ratio of sediment transported (SDR) on slope was dependent on land use patterns. Compared with the fallow naked slope, SDR decreased by about thirty percent in land with crops planted in the same direction as slope. The reason of decreased soil loss under condition of vegetation was the reduced SDR.